Prenatal thrombosis of renal veins and the inferior vena cava in a newborn with double heterozygosity for the factor V Leiden and prothrombin gene G20210A mutations: a case report. Issue 2 (March 2018) - Bulut, Ozgul; Ince, Zeynep; Uzunhan, Ozan; Coban, Asuman
Abstract : N/A: Renal vein thrombosis in a neonate is a rare but well recognized condition with low mortality but high morbidity. The cause has not been explained clearly yet but is probably a multifactorial process that includes inherited prothrombotic abnormalities. Antenatal onset of renal vein thrombosis is important due to the increased risk for permanent organ damage. We report a case of prenatal thrombosis of the renal veins and the inferior vena cava in a newborn with double heterozygosity for factor V Leiden and prothrombin gene mutations who had persistently impaired renal function requiring chronic peritoneal dialysis.